Correlation Between Resting Theta Power and Cognitive Performance in Patients With Schizophrenia - Cao, Yanxiang; Han, Chuanliang; Peng, Xing; Su, Ziyao; Liu, Gan; Xie, Yixi; Zhang, Yiting; Liu, Jun; Zhang, Pei; Dong, Wen; Gao, Michel; Sha, Sha; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Schizophrenia is a mental disorder that is characterized by progressive cognitive impairment. Objective measures of cognitive function may provide reliable neurobiomarkers for patients with schizophrenia. The goal of the current work is to explore the correlation between resting theta power and cognitive performance in patients with schizophrenia. Methods Twenty-two patients with schizophrenia and 23 age-, sex-, and education-matched healthy controls were included in this study. The MATRICS Consensus Cognitive Battery (MCCB) was used for cognitive evaluation and the Positive and Negative Syndrome Scale (PANSS) for evaluation of clinical symptoms. EEGs were acquired in the resting state with closed and opened eyes. Between the two groups, we compared the relative theta power and examined their relationship with cognitive performance. Results Compared to healthy controls, patients with schizophrenia showed significantly higher theta power, both with eyes closed and open (P < 0.05). When the eyes were open, negative correlations were found in patients with schizophrenia between theta power in the central and parietal regions with processing speed scores, and between the theta power of the Pz electrode and verbal learning and reasoning and problem-solving scores (r≥-0.446). In the control group, theta power over the Fz electrode was negatively correlated with processing speed (r=-0.435). Conclusions Our findings showed that theta activity increased in certain brain regions during resting state in schizophrenia. Negative associations between resting theta power (increased) over the parietal-occipital regions with MCCB domains scores (decreased) suggest that altered theta activity can be used as a neurobiological indicator to predict cognitive performance.